Interference and threshold level of Sida rhombifolia on Chenopodium quinoa Willd. crop (Bioagro, 2024)
Studies on interference and economic threshold level (TL) of weeds on quinoa are scarce. Thus, the goal of this study is to determine the interference and the TL of Sida rhombifolia (arrowleaf sida) on quinoa varieties. The experiment was organized using a completely randomized design, with four replicates. The treatments were composed of quinoa varieties (Q 1303, Q 1331 and Q 1324) in competition, respectively, with ten densities of arrowleaf sida (0, 12, 16, 18, 128, 252, 432, 524, 584, and 756; 0, 24, 88, 104, 112, 124, 160, 164, 260 and 320; 0, 16, 72, 104, 116, 144, 156, 160, 228 and 304 plants m-2). The variables evaluated were: plant density, soil coverage, leaf area, dry mass of weed shoots; and the variables related to quinoa were: grain yield, control cost, price per bag and control efficiency. Quinoa variety Q 1303 showed greater competitive ability with arrowleaf sida than Q 1331 and Q 1324. The values of TL varied from 1.79 to 11.60 plants m-2 for the Q 1303 variety, which demonstrated higher competitiveness with arrowleaf sida, while the lowest TL values varied from 0.80 to 6.91 plants m-2 for Q 1234 and Q 1331 varieties, showing less competitiveness in presence of the competitor. The TL values decreased with the increases in grain yield, in the price of the quinoa bag, in the efficiency of weeding and in the reduction of the control cost of arrowleaf sida, justifying the adoption of weed control measures.
Keywords: Arrowleaf sida; competitive ability; interaction between plants; quinoa